Osseous variability around the elbow joint. (April 2023) - Kunc, Vojtech; Salavova, Sarka; Kachlik, David
There are many osseous variants that occur around the elbow joint such as supracondylar process, supratrochlear foramen, accessory ossicles, and others. Scientific databases were searched for variants around the elbow joint. Elbow radiographs from our center demonstrating some of these findings were included in the study. The aim of the present review was to provide comprehensive information on the terminology, prevalence, history, etiology, and clinical importance of these variants. These anatomical variants are important for radiologists while interpreting radiographs, computed tomography, and magnetic resonance imaging for trauma and orthopedic surgeons during osteosynthesis at the distal humerus, proximal ulna, and radius.